دور مستشار التوجيه والارشاد المدرسي والمهني في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي - أحمودة, آمال (جامعة الوادي university of Eloued, 2022)
الملخص: هدفت هذه الدراسة إلى الكشف عن دور مستشار التوجيه والارشاد المدرسي في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي، ولهذا الغرض انطلقت هذه الدراسة من تساؤل رئيسي مفاده: - هل لمستشار التوجيه والارشاد المدرسي دور في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي؟ وقد تفرع عن هذا التساؤل مجموعة من التساؤلات الفرعية تمثلت فيما يلي: - هل يساهم مستشار التوجيه والارشاد المدرسي من خلال دوره في المتابعة والاشراف في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي؟ - هل يساهم مستشار التوجيه والارشاد المدرسي من خلال دوره الاعلامي في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي؟ - هل يساهم مستشار التوجيه والارشاد المدرسي من خلال دوره الارشادي في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي؟ - هل توجد معوقات وظيفية تحول دون قيام مستشار التوجيه والارشاد المدرسي بأدواره للتخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي؟ وقد اعتمدنا في هذه الدراسة على المنهج الوصفي نظرا لتماشيه مع موضوع الدراسة, في حين تمثل مجتمع الدراسة في مستشاري التوجيه والارشاد المدرسي للتعليم الثانوي, ونظرا لعددهم القليل تم الاعتماد على أسلوب الحصر الشامل, وللحصول على المعطيات الميدانية تم الاستعانة بأداة الاستبيان وقد احتوى على 36 بندا وتوصلت الدراسة الى النتائج التالية: - لمستشار التوجيه والارشاد المدرسي دور في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي . - يساهم مستشار التوجيه والارشاد المدرسي من خلال دوره في الاشراف والمتابعة في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي. - يساهم مستشار التوجيه والارشاد المدرسي من خلال دوره الاعلامي في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي. - يساهم مستشار التوجيه والارشاد المدرسي من خلال دوره الارشادي في التخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي. - توجد معوقات وظيفية تحول دون قيام مستشار التوجيه والارشاد المدرسي بأدواره للتخفيف من المشكلات التربوية لدى تلاميذ الطور الثانوي. Résumé : فرنسية أو انجلزية This study aimed to reveal the role of the school guidance and counseling advisor in alleviating the educational problems of secondary school students, and for this purpose this study started from the following problem question That: - What is the role of the school guidance and counseling advisor in alleviating the educational problems of secondary school students? from the above question at set of sub-questions emerged: - Does the school guidance and counseling advisor, through his role in follow-up and supervision, contribute in alleviating the educational problems of secondary school students meet? - Does the school guidance and counseling advisor, through his role his media awareness contribute to alleviating the educational problems of secondary school students meet? - Does the school guidance and counseling advisor, through his guidance role, contribute in alleviating the educational problems secondary school students meet? - Are there any functional obstacles and constraints that prevent him on her from playing his role? The study is carried out using the descriptive approach due to its consistency with the nature of the study, Our sample informants consists of the secondary ,in the present study we adopted the comprehensive inventory method In order to collect data, we distributed a questionnaire which contains 36items. The study reached the following results: - the school guidance and counseling advisor have a role in the educational problems of secondary school students - the school guidance and counseling advisor have a role in the educational problems of secondary school students - The school guidance and counseling advisor, through his role in supervision and follow-up, contributes to alleviating the educational problems of secondary school students meet. - The school guidance and counseling advisor, through his media awareness role, contributes in alleviating the educational problems of secondary school students. - The school guidance and counseling advisor, through his guidance role, contributes in alleviating the problems met by secondary school students. - The school guidance and counseling advisor, faces some obstacles and constraints which prevent him from doing his appropriately . - the school guidance and counseling advisor have a role in the educational problems of secondary school students.
مذكرة ماستر علم الإجتماع تخصص علم الاجتماع التربية
Keywords: مستشار التوجيه، الإرشاد المدرسي، المشكلات التربوية; Conseiller d'orientation, orientation scolaire, problèmes scolaires; Guidance counselor, school counseling, educational problems